2016
DOI: 10.5177/ntvt.2016.03.15240
|View full text |Cite
|
Sign up to set email alerts
|

The (putative) pathological impact of fibromyalgia on the orofacial system

Abstract: Onderzoek en wetenschap InleidingFibromyalgie is een gecompliceerd syndroom zonder aanwijsbare etiologie dat wordt gekenmerkt door uitgebreide diff use, chronische musculoskelettale pijn die vaak samengaat met vermoeidheid, geheugenproblemen, stemmingsproblemen en slaapstoornissen. Patiënten met fi bromyalgie hebben vaak eerder chronische pijn ervaren. Veelvoorkomende problemen zijn hoofdpijn, dysmenorroe (menstruatiepijn), pijn door temporomandibulaire disfunctie, endometriose (slijmvlies van de uterus dat zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Rhodus et al 18 outlined that dysphagia can occur in conjunction with other oral symptoms in this population. These symptoms include xerostomia, glossodynia dysgeusia and odynophagia, a point which was also emphasised by De Baat et al 19 These studies highlight the currently ambiguous nature of the relationship between fibromyalgia and dysphagia, and the need for further investigation into the causation and presentation of this condition. The sparse amount of research into this topic was re-emphasised recently in a systematic review, which found a very limited number of available studies which investigated dysphagia in those with fibromyalgia.…”
Section: Dysphagiamentioning
confidence: 78%
“…Furthermore, Rhodus et al 18 outlined that dysphagia can occur in conjunction with other oral symptoms in this population. These symptoms include xerostomia, glossodynia dysgeusia and odynophagia, a point which was also emphasised by De Baat et al 19 These studies highlight the currently ambiguous nature of the relationship between fibromyalgia and dysphagia, and the need for further investigation into the causation and presentation of this condition. The sparse amount of research into this topic was re-emphasised recently in a systematic review, which found a very limited number of available studies which investigated dysphagia in those with fibromyalgia.…”
Section: Dysphagiamentioning
confidence: 78%
“…Fujarra et al (46) evaluated TMJ disorder symptoms in FMS patients and found that FMS patients were suffering TMJ symptoms with muscle disorders, disc displacement and myofascial pain with limited mouth opening. Oral manifestations of FMS, such as TMJ dysfunction, xerostomia, hyposalivation and burning mouth syndrome have also been suggested (34,47). Ghurye and McMillan (48) also suggested that pain in the TMJ might be associated with other chronic pain conditions such as FMS, irritable bowel syndrome and migraine.…”
Section: Discussionmentioning
confidence: 99%